Two-isophorone fluorophore-based design of a ratiometric fluorescent probe and its application in the sensing of biothiols. Issue 37 (4th September 2019) - Wang, Chengcheng; Wang, Yang; Wang, Guanyang; Chen, Shangjun; Huang, Chusen
Abstract : A newly designed ratiometric fluorescent probe is applied in the sensing of biothiols. Abstract : 2, 4-Dinitrobenzenesulfonyl (DNBS) has been widely used for the design of small fluorescent probes for biothiols due to its high reactivity. However, most DNBS-based fluorescent probes exhibit "off–on" fluorescence response towards biothiols due to the strong quenching effects of DBNS on the fluorophores. Herein, we present an alternative design of a ratiometric fluorescent probe based on DNBS for biothiols. A new fluorophore bearing two isophorone malononitrile structures was conjugated with DNBS to provide a target probe (CHT ), which exhibited a ratiometric sensing behavior towards biothiols. The sensing process is rapid and highly selective. Most importantly, CHT has high stability in the quantitative detection of Cys compared to the control probe CHM, which performed an "off–on" sensing for biothiols. Endogenous biothiols were successfully monitored with CHT in live cells through the ratiometric fluorescence signal. This new fluorophore bearing two isophorone malononitrile moieties will pave a new avenue to design ratiometric fluorescent probes for imaging and quantitative detection.